PRAKTEK SUAP/ PUNGLI DI BIDANG PENGANGKUTAN BARANG DAN/ ATAU ORANG DI KOTA BEKASI (STUDY TENTANG PERILAKU MENYIMPANG PADA BISNIS ANGKUTAN DARAT) - , Patar Ferdinand ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Transportation is one of the vital activity in society economic activities. Transportation will support national development in various sectors, therefore the rule of law in the transport sector must be guaranteed by a government that is supported by the Bussinesman and Society. The government must ensure the transport sector entrepreneurs to develop their business effectively and efficiently so that people feel the organization of transport that is safe, comfortable and affordable. In practice occurred, (individually actors) that Government should be located as planners, regulators, controllers and supervisors are still many areas of the transport behavior of corrupt conduct and illegal âmeelâ. The high level of corruption would lead to economic costs so high due to the owner of the goods (businessesman) to charge all fees, entertainment expenses, and other costs into the selling price of the component goods and services that will be suffered by the consumen. The researcher would like to answer the main factors of âmeelâ corrupt behavior and extortion that occurred in the field of transportation of goods/people in Bekasi and the remedies of that deviant behavior.